PEMBELAJARAN KOLABORATIF PADA MATA PELAJARAN BAHASA INDONESIA DI SMK NEGERI 1 KOTABUMI - Dewi Ratnaningsih; Septiana Septiana (Universitas Muhammadiyah Kotabumi, 2019)
The problem that will be examined in this article is collaborative learning in Indonesian language subjects at SMK Negeri 1 Kotabumi. The purpose of writingis to describe the application of collaborative learning in Indonesian language subjects at SMK Negeri 1 Kotabumi. Based on the results of reflection, obtainedsome lessons learned such as: a) collaborative learning tools development resulting in more directed learning plan designs, interactive learning media, and more interesting teaching materials, b) the application of teaching collaboration between teachers and lecturers makes the evaluation process learning is better covered, c) the use of collaborative learning methods opens space for teachers and lecturers to discuss so as to improve cooperative skills and improve the quality of learning in schools.